E-Commerce product comparison portal for classification of customer data based on data mining. (2022) - Sharma, Dilip Kumar; Lohana, Sarika; Arora, Saurabh; Dixit, Ashutosh; Tiwari, Mohit; Tiwari, Tripti
Abstract: In this search paper scrapping the data such as product name, product price, product reviews and ratings related to suggested products from Flipkart and Amazon using Robotic Process Automation tool and data is cleaned in order to remove noisy values and based on the user request the products from Flipkart and Amazon is suggested on E-Commerce portal based on user preferences the user can purchase the product from any site which is completely dependent on user. The RPA tool i.e., UiPath is used to create software robot for both Flipkart and Amazon, this bot is used to scrape the data from Flipkart and Amazon and perform cleaning operation and dump the data to database which can be used for future use. And the bot can be triggered on daily basis for data collection for database updation. This E-Commerce portal helps to categorize and distinguish the product purchase behavior and satisfy the end customer requirements.